Direct reconstruction of qualitative depth information from turbid media by a single hyper spectral image - Hohmann, Martin; Hecht, Damaris; Lengenfelder, Benjamin; Klämpfl, Florian; Schmidt, Michael (Proc. SPIE 10885, Optical Diagnostics and Sensing XIX: Toward Point-of-Care Diagnostics, 2019)
For diagnostic imaging, a modality is required which has to be quick, inexpensive and noninvasive. Furthermore, risks for the patients have to be kept as low as possible since repetitive imaging might be required. To enable risk free imaging, hyper spectral imaging as tool for 3D tissue imaging is proposed to potentially meet all the above mentioned requirements. In this study, the first results of three dimensional reconstructions of hyper spectral images are presented. In general, the back reflected image consists of information from many different depths such that inclusions in different depths have a different effect on the back reflected images. Moreover, due to the wavelength dependent penetration depths, the spectral composition of the back reflected image changes in a different manner for different depths. This difference is normally not linear. However, due to a fine spectral resolution the difference can be assumed to be linear. The partial derivative of the wavelength is thus supposed to show the difference and allow the analysis. To demonstrate this, polyurethane phantoms are manufactured with TiO2 as scatterer and ink as absorber. The inclusions are simulated by drilling holes into the phantom. The phantoms are imaged with a hyper spectral camera with a resolution of 51x765x1450 voxel (x, y, λ) from 400 to 800 nm. The spectral resolution due to the aperture is about 3 nm. In this study, first results are presented and a qualitative depths reconstruction is demonstrated. It is possible to show which inclusion is deeper with respect to the othe
Keywords: Hyperspactral Imaging